The remembering subjectivity - María Angélica Garzón Martínez (Revista Colombiana de Sociología, 2015)
Remembrance subjectivity is perhaps that which corresponds to the era of memory increase in which remembering is obligatory. This is the main hypothesis of the article, which is derived from different readings concerning the exercise of remembering, narrating, and constructing collective memory. In that sense, a theoretical-type of reflection emerges that enquires into what is called remembrance subjectivity, the firm lines that cross it and how it materializes into a witness figure. For all this one takes up anew some of Foucault’s ideas which indicate that political, economic and existential conditions configure subjects and relations of truth. Based on the aforementioned, one can emphasize the so-called subjective trend and the testimonial boom to analyze those subjects and truth relations in light of the construction of memories (plural) and the function of the memory or, in Ricoeur’s words, the imperative “you will remember”. At the end, one develops a platform concerning how remembrance subjectivity via the narration of the memory subverts the idea of its production in order to establish creative tactics that will permit transporting a memory exclusive to the past to a memory that permits the construction of political claims. Along this line of thought, the central category of analysis is identified as a space not only of the production of subjectivity but also as a creation of it, in which narration of the past permits self-reflection and a reading of the subject as an active agent of social change. Therefore, the construction of remembrance subjectivity allows the social agents to overcome the logics of “cosification” and reclaim a place in the world or, in other words, a social position and a role in history. More concretely this article presents the idea of remembrance subjectivity that becomes converted into a political platform for reclaiming the right to recollect and change based on those recollections